Validation of Blended Potential Flow Model for Lifting Rotors with Wake Contraction - Huang, Jianzhe; Peters, David A. (Journal of Applied Nonlinear Dynamics, 2026)
Dynamic wake models have been evolved from the earliest, threedegree- of-freedom models (derived from momentum theory) to full finite-state models derived from potential flow theory by a formal Galerkin method. These models are widely used in industry, but still have some drawbacks that need to be remedied. These drawbacks include: 1.) lack of good convergence both on the disk and off the disk (one can use one or the other but not both), 2.) poor results downstream in the limit of shallow skew angles, 3.) poor convergence inside of the rotor wake, 4.) lack of the effect of wake contraction. In this paper, a blended model adopted applications of adjoint theorem, a special change of variables to overcome these obstacles. The resultant model is well behaved in all regimes and is applicable to use in realistic problems of flight simulation.